The Correlation between Trust and Security, Attitude and, Perceive Usefulness towards Online Payment Practice among UTHM Diploma Students - Hairuddin, Hafisah; Md Nasir, Siti Aisyah; Juma'at, Nuramirah; Norain Ahmad Nordin (Multidisciplinary Applied Research and Innovation, 2025)
The foremost aim of this study is to assess the percentage of awareness and practices of online payment methods among the Universiti Tun Hussein Onn Malaysia (UTHM) diploma students, to determine the factors affecting the use of online payments among UTHM diploma students and to identify the relationship between the percentages of awareness and practice of online payment methods and the factors affecting the use of online payments. This research used the survey methods which the questionnaire was distributed to UTHM diploma students by using Google Form via WhatsApp and Telegram. The questionnaire consists of 4 sections: demographic, trust and security, attitude and perceive usefulness. The collected data was analysed by using Statistical Package for Social Science (SPSS). From this research, we were able to access the percentage of awareness which 95.5% from the respondent do aware about online payments and there is 51.5% of the respondents who practices online payments every day. The correlation of the factors affecting the use of online payments was also determined where attitude has a Pearson Correlation Coefficient of 1, which is very high, which means that attitude contributes the most for the use of online payments within UTHM Diploma Students. We also know that familiarity against the other variables, it is shown that only security has no significant correlation with the familiarity variable. Besides, for familiarity against the other variables, it is shown that only security has no significant correlation with the familiarity variable. The P-Value for security is higher than 0.05 which will cause an acceptance to null hypothesis. However, despite having significant correlation, all of the variables have a weak correlation with the familiarity variable.